2021
DOI: 10.48550/arxiv.2106.04457
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On Lyubeznik type invariants

Abstract: We discuss for an affine variety Y embedded in affine space X two sets of integers attached to Y ⊆ X via local and de Rham cohomology spectral sequences. We give topological interpretations, study them in small dimension, and investigate to what extent one can attach them to projective varieties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Earlier, Dao and Takagi, inspired by remarks of Varbaro, showed that over any field, Serre's condition S 3 implies that λ d´1,d " 0, [DT16], while in increasing generality it was shown in [Wal01b,Lyu06a,Zha07] that rκpAq ě dimpAq ´1s ô rλ d,d pAq " 1s. In [RWZ21] are some other results on the effect of Serre's conditions pS t q on ΛpAq. 4.4.2.…”
Section: 22mentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier, Dao and Takagi, inspired by remarks of Varbaro, showed that over any field, Serre's condition S 3 implies that λ d´1,d " 0, [DT16], while in increasing generality it was shown in [Wal01b,Lyu06a,Zha07] that rκpAq ě dimpAq ´1s ô rλ d,d pAq " 1s. In [RWZ21] are some other results on the effect of Serre's conditions pS t q on ΛpAq. 4.4.2.…”
Section: 22mentioning
confidence: 99%
“…We note in passing that there are algorithmic methods that can compute the pages of this spectral sequence as vector spaces over C, see [OT99, Wal00, Wal01a, OT01]. In the sequence (4.2.1.1), the Tor-groups involved vanish for the index exceeding dim X, and so the spectral sequence operates clearly inside the rectangle 0 ď i ď lcd R pIq, 0 ď j ď n. However, it is actually limited to a much smaller, triangular region, compare [RWZ21].…”
Section: Some Examples and Conjecturesmentioning
confidence: 99%
See 2 more Smart Citations